Price, volume and volatility effects associated with derivative warrant listing on the Singapore Exchange. - Ke, Peishan. (2008)
This paper examines the effect of the listing of derivative warrants on the price, volatility and liquidity of the underlying shares on Singapore Exchange (SGX) from January to September 2006. Our sample of 338 derivative warrants shows significant negative returns occurred for days prior to their listing dates. We postulate that this evidence supports that the high gearing nature of derivative warrants causes investors to unload their equity holdings and subsequently purchase derivative warrants to gain similar exposure to the underlying shares. In addition, we found that there is excess volatility prior to the listing of derivative warrants and this could be due to speculation. While there is an increase in trading volume, which signifies additional liquidity, bid-ask spread also significantly widened in the window period both prior to and after the listing of the derivative warrants. This could be explained by additional information asymmetry that caused the market makers to require additional compensation for taking positions against more informed traders.